Getting Ready To Conduct Scientific Writing: Academic Search Engine As Personal Learning Environment (PLE) Assistance - A’thi Fauzani Wisudawati; Dian Palupi; Jannatul Laily Noviabahari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
At the point when the students are assessed, they are demanded to work to publish scientific writing. This study investigates the process of constructing scientific writing as well as the academic search engine that is frequently used by graduate students in building their papers. Later on, this study also discloses the factor of using repeated platforms. A personal learning environment helps the students to connect both inside and outside the classroom learning by employing digital tools. This paper presents a case study exploring the steps of conducting scientific writing, the academic search engine mostly used by students, and the factors in deciding the platform. Eighteen graduate students majoring in the English education department were the participants of this study. The data was collected through class observation, questionnaires, and semi-structured interviews. The result shows several steps to construct scientific writing including readiness, composing the article, getting ready for publication, distribution, and development. While Google Scholar (100%), Web of Science (94.7%), and online library (63.2%) are the top three online platforms as the academic search engine they used to search for references to build arguments for their scientific writing. Some factors why those platforms become highly beneficial are exposed by the participants such as their pertinence, reference quality, and publication impact. This study is expected to provide certain considerations for students or scholars about utilizing several online platforms and some reasons behind which is beneficial to build scientific writing publications.